High Strain Rate Response of 7055 Aluminum Alloy Subject to Square-spot Laser Shock Peening - Sun, Rujian; Zhu, Ying; Li, Liuhe; Guo, Wei; Peng, Peng (IOP conference series. Materials Science and Engineering, 2017)
The influences of laser pulse energy and impact time on high strain rate response of 7055 aluminum alloy subject to square-spot laser shock peening (SLSP) were investigate. Microstructural evolution was characterized by OM, SEM and TEM. Microhardness distribution and in-depth residual stress in 15 J with one and two impacts and 25 J with one and two impacts were analyzed. Results show that the original rolling structures were significantly refined due to laser shock induced recrystallization. High density of microdefects was generated, such as dislocation tangles, dislocation wall and stacking faults. Subgrains and nanograins were induced in the surface layer, resulting in grain refinement in the near surface layer after SLSP. Compressive residual stresses with maximum value of more than -200 MPa and affected depths of more than 1 mm can be generated after SLSP. Impact time has more effectiveness than laser pulse energy in increasing the magnitude of residual stress and achieving thicker hardening layer.